The Leadership Effectiveness of Behavioral Cognitive Therapy on Academic Anxiety in Children / Efektivitas Terapi Kognitif Perilaku terhadap Kecemasan Akademik Anakf Parent and Teacher in Islamic Education - Laily Abida; Umi Salamah (Al-Mudarris: Journal Of Education, 2021)
Academic anxiety is often experienced by children in the learning process. have a negative impact on children's academic abilities at school. Parents and teachers are expected to make appropriate efforts to overcome this academic anxiety problem so that children are able to make positive achievements in learning. The method used in this study is a qualitative method with a literature study approach, the sources taken are scientific books and research results that have been published as reference materials, with the aim of knowing the effectiveness of cognitive behavioral therapy to overcome academic anxiety disorder in children. . The results of the study stated that cognitive behavioral therapy was proven to reduce the level of academic anxiety in children